Antifungal and antibiofilm activity of crude hydroalcoholic extract and fractions of Myrcia neoobscura leaves against a clinical isolate of Candida krusei - Leticia Bachmann; Eduarda Rensi Botelho; Patrícia Helena Arrabal; Pâmela Elise Munzlinger; Patryne Luana da Silva Dantas; Larissa Mascarenhas Krepsky; Lucas Ferriolli Mariotto; Michele Debiasi Alberton; Tatiani Karini Rensi Botelho (Frontiers in Natural Products, 2026)
Infections caused by biofilm-forming Candida sp. Are responsible for high morbidity and mortality rates. With the scarcity of therapeutic options and the increase in resistance to antifungal drugs, new treatment options are needed. Myrcia neoobscura is a tree endemic to the Atlantic Rainforest, belonging to the genus Myrcia , several of whose species have demonstrated important antifungal activities. The aim of this study was to evaluate the antifungal and antibiofilm activity of the crude hydroalcoholic extract and fractions of Myrcia neoobscura , as well as the mechanisms of action using in vitro methods. Strong inhibitory results were observed against one clinical isolate of Candida krusei with the aqueous fraction standing out (MIC of 7.81 μg/mL), followed by crude hydroalcoholic extract, ethyl acetate, insoluble fractions (15.62 μg/mL), hexane and dichloromethane fractions (62.50 μg/mL). Regarding the mechanism of action, the increase of MIC values on both Ergosterol and Sorbitol assays suggest that extract and fractions of M. neoobscura acts on fungal membrane and cell wall. Candida krusei showed moderate biofilm formation and significant antibiofilm activity were observed for all tested samples against the mature biofilm, with the dissolution of 48h mature C. krusei biofilm ranging from 45.6% up to 60.2%. These findings highlight M. neoobscura as a promising source of antifungal and antibiofilm agents, particularly against C. krusei .